2010
DOI: 10.1007/s00009-010-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

Measure-Preserving Functions and the Independence Copula

Abstract: We solve a problem recently proposed by Kolesárová et al. Specifically, we prove that a necessary and sufficient condition for a given copula to be the independence or product copula is for the pair of measure-preserving transformations representing the copula to be independent as random variables.We provide examples of such pairs for the well-known Cantor, Peano, and Hilbert curves. Moreover, a general constructive method is given for the representation of copulae in terms of measure-preserving transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We introduce a number representation system which generalizes another system of representation B used by the authors in [2]. The new system is also denoted by B, and it is defined as follows:…”
Section: Relationship Between Cantor and S A Functionsmentioning
confidence: 99%
“…We introduce a number representation system which generalizes another system of representation B used by the authors in [2]. The new system is also denoted by B, and it is defined as follows:…”
Section: Relationship Between Cantor and S A Functionsmentioning
confidence: 99%
“…Proof. We shall prove only (7) which shows that µ * ν is a doubly stochastic measure when the measures µ and ν are doubly stochastic and inducible by copulas. Let A and B be copulas and…”
Section: On (A B)mentioning
confidence: 95%
“…One such case is the case of bivariate complete dependence copulas. And if we assume that the random variables are uniform on [0, 1], there is a measure-preserving transformation on [0, 1] connecting the two random variables. It has been observed that the graph of such a function and the support of the corresponding copula are closely related.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the graph of such a function and the support of the corresponding copula are closely related. For instance, it has been shown in [2] that the mass of a copula is concentrated on the graph of a corresponding function (V C (gr f ) = 1). In our work, we obtain that the support of such copula is an essential closure of the graph of a "refinement"of the function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation